Implementasi Sistem Pakar Menggunakan Metode Certainty Factor Dalam Mendiagnosa Penyakit Pencernaan - Arvianto, Ramdani (JATISI, 2025)
Digestive disorders are common health problems in society. However, many individuals choose to ignore the symptoms they experience for various reasons, such as fear of a serious diagnosis, concern that stress may worsen the condition, or the hope that the symptoms will resolve on their own. On the other hand, limited access to medical services also poses a challenge in early treatment. Meanwhile, the similarity of symptoms across different digestive diseases also makes self-diagnosis challenging. This study developed a web-based expert system to assist in identifying diseases based on symptoms experienced. The system was developed using the Waterfall model with the Python programming language and the Certainty Factor method in the diagnostic process. Symptom, disease, and solution data were obtained from the Halodoc, Alodokter, Klikdokter, and HelloSehat websites, then validated through interviews with experts. Black-box testing results showed that all features functioned as expected, while expert validation demonstrated good accuracy and system reliability. The system is capable of providing diagnosis results based on symptom input quickly, accurately, and easily, thereby assisting users in conducting initial self-diagnosis of digestive diseases.